1998
DOI: 10.1046/j.1525-1497.1998.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory versus inpatient rotations in teaching third-year students internal medicine

Abstract: We studied 63 randomly selected third-year students who split their 10-week medicine clerkship between ambulatory and inpatient components. Compared with their inpatient experience, during the ambulatory rotation, the 63 students felt more like doctors, more responsible for patients, and more able to know and help their patients. Students reported that ambulatory attending staff appeared happier and less stressed, and did not embarrass them as frequently. Compared with their 619 "inpatient" classmates, these 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
2
19
1
2
Order By: Relevance
“…[1][2][3] Designed to ensure that students acquire fundamental skills needed for further specialty training, these clerkships involve a complex interaction between student and teacher that is often described as an apprenticeship. 4 The student is acquiring the skills of a physician by doing the work of patient care.…”
mentioning
confidence: 99%
“…[1][2][3] Designed to ensure that students acquire fundamental skills needed for further specialty training, these clerkships involve a complex interaction between student and teacher that is often described as an apprenticeship. 4 The student is acquiring the skills of a physician by doing the work of patient care.…”
mentioning
confidence: 99%
“…Tutors enjoy teaching in the ambulatory care setting (Kalet et al, 1998). In our experience tutors interacted well with both students and patients and were reported to be at ease in the new teaching environment.…”
Section: Tutorsmentioning
confidence: 68%
“…A study of medical students found that those students who had increased time on ambulatory rotations had a more positive experience, and scored as well on objective measures of learning, as students with mostly inpatient rotations. 20 A survey of medical clerkship directors recommended onethird of medical student time be spent in ambulatory care compared with 50% in the inpatient setting. 21 The relative benefits for residents may be different, however: in one study at an academic medical center residents gave better evaluations to inpatient than outpatient teaching physicians.…”
Section: The Balance Between Inpatient and Outpatient Trainingmentioning
confidence: 99%